Formulasi dan Kesantunan Tindak Tutur Izin ke Kamar Mandi dalam Bahasa Indonesia - Mijianti, Yerry; Afrizal, Mohamad (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
Asking for permission to go to the bathroom is a common linguistic practice in daily interactions, yet it carries complex pragmatic implications as it involves both individual needs and the orderliness of social interaction. This study aims to describe the formulation of bathroom permission speech acts in Indonesian and the pragmatic impact of these formulations on interaction. The study focuses on lexical variations, speech forms and structures, politeness strategies, and the acceptability of utterances across various interactional contexts. A qualitative approach with field research methods was employed. Oral data of bathroom permission utterances were collected through Discourse Completion Tasks (DCT), in-depth interviews, and covert field experiment. The data were analyzed using descriptive pragmatics, considering the speech situation, formulation structure, and the hearer's response. The results indicate that bathroom permission formulations are dominated by euphemistic locational references with the three most dominant lexicons being ke belakang (going to the back), ke kamar mandi (going to the bathroom), and toilet, and realized through indirect speech. The speech structure is graded according to the level of formality, ranging from complete structures in formal contexts to minimal structures in everyday settings. Furthermore, verbal and non-verbal politeness strategies play a crucial role in maintaining utterance acceptability and interactional flow, positioning bathroom permission as a socially negotiated cooperative interruption. Theoretically, this study contributes to the development of formulaic language studies in Indonesia by mapping social routine speech patterns that bridge individual biological needs with cultural politeness norms.